Trawling and creeling for nephrops: impacts on biodiversity and populations structure - Marques, Lino Alexandre António (2015)
Dissertação de mestrado, Aquacultura e Pescas, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015 The Norway Lobster (Nephrops norvegicus) is a deep- water burrowing decapod crustacean with a widespread distribution ranging from Iceland, the Faroe Island and northwestern Norway to the south Atlantic coast of Morocco with a patchy distribution on the Mediterranean Sea. In the Portuguese shelf and slope areas, adults are found on depths ranging from 90 to 800 m depth. The distribution of this species seems to be limited to high percentage of mud bottoms. Along the years this species acquired some importance in the fisheries sector due to its market value. It is nowadays one of the main species in crustaceans’ bottom trawling in Europe. The fishing activity for the exploitation of this species has shown some environmental impacts. In particular, trawl fisheries are known to directly impact the bottoms, and are associated with considerable amounts of bycatch and discards. Recently, the European community has turned the attention to creel fishery for Nephrops, encouraging the change from trawl to creel in this fishery in order to reduce the bycatch. During this study it was possible to observe that there is a clear difference between both gears in what respects the commercial value of Nephrops caught as well as in terms of species affected by the gears. O lagostim (Nephrops norvegicus) é um crustáceo bentónico de águas profundas, com uma distribuição ampla que se estende desde a Islândia, as Ilhas Faroé e o noroeste da Noruega até a costa atlântica sul de Marrocos e ainda uma distribuição em bolsas dispersas no Mar Mediterrâneo. Os indivíduos adultos de Nephrops norvegicus podem ser encontrados nas zonas de plataforma continental e no talude entre os 90m e os 800m de profundidade em águas portuguesas. A distribuição nesta espécie pode ir desde fundos de vasa compacta ate fundos de vasa arenosa. Ao longo dos anos esta espécie adquiriu alguma importância no sector das pescas devido ao seu crescente ...